Correlations Between Clinical Features and Mouth Opening in Patients With Systemic Sclerosis - İpek TÜRK,; Nihan CÜZDAN,; Volkan ÇİFTÇİ,; Didem ARSLAN,; İlker ÜNAL, (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the correlations between clinical features and mouth opening in patients with systemic sclerosis (SSc). Patients and methods: Eighty patients with SSc (13 males, 67 females; mean age 53.39±11.65 years; range, 31 to 76 years) followed in our clinic were enrolled in the study. Skin involvement was assessed using the modified Rodnan skin score (mRSS), joint/tendon involvement with finger-tip to palm (FTP) distance and interstitial lung disease (ILD) was evaluated with clinical and radiologic methods. The interincisal distance (ID) measurement was used to assess the maximal mouth opening capacity. We examined associations between the ID and clinical features of SSc. Results: The ID was lower in females compared with males, and in diffuse type compared with the limited type (p<0.001 and p<0.001, respectively). A significant negative correlation was found between the ID with mRSS and FTP distance (p<0.001 and p=0.001, respectively). The ID was lower in patients with ILD than in patients without ILD (p=0.006). A formula was constituted to predict the maximal mouth opening of the patient with regression analysis. According to the formula, being male was associated with an increase of 6.14 mm, the presence of ILD with a decrease of 3.19 mm, every 10 mm increment in mRSS with a decrease of 3.72 mm and FTP distance >0 mm with a decrease of 5.13 mm in mouth opening. Conclusion: Microstomia is associated with low quality of life in patients with SSc. In our study, sex, ILD, mRSS, and FTP distance were observed to be the most important factors that were related with mouth opening in patients with SSc.